Analysis of Radial Force and Vibration Energy in a Centrifugal Pump. (20th July 2020) - Cui, Baoling; Li, Jiacheng; Zhang, Chenliang; Zhang, Yingbin
Abstract : Vibration is one of the main issues taken into consideration in the design and manufacture of the pump. The radial force and vibration of the impeller induced by fluid in a centrifugal pump were investigated at different flow rates by numerical simulation. The vibrations on the volute were measured by the experiment. The variation trend of the radial displacements of the impeller is consistent with that of the radial forces, and the variation in the radial displacement lags that of the radial force. The vibration energies on the impeller and the volute were analyzed based on root-mean-square (RMS) values in the frequency domain. The distributions of energy loss in the pumps were calculated to determine the total entropy generation (TEG) and entropy generation rate (EGR). The TEG values as calculated are in close accordance with hydraulic loss. The vibration is a result of the poor flow patterns and consequently results in increased energy losses in the pump.